Effect of Time of Sowing on the Yield and Yield Attributes of Barley Under Rainfed Condition (Bangladesh Journal of Scientific and Industrial Research, 2007)
No Abstract available.Bangladesh J. Sci. Ind. Res. 41(1-2), 113-118, 2006